The Role of Local Government Financial Performance in Reducing Unemployment Through Economic Growth In Bengkulu Province - Witri Ariyanti; Rini Indriani; Saiful (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2026)
This study analyzes the impact of local government financial performance on economic growth and unemployment rates, while also investigating the mediating role of economic growth. A quantitative approach is employed, utilizing panel data from 10 districts/cities in Bengkulu Province over the period of 2020–2024, resulting in a total of 50 observations. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The findings indicate that local government financial performance has a significant negative effect on economic growth and a significant positive effect on the unemployment rate. Furthermore, economic growth does not exert a significant effect on the unemployment rate and does not mediate the relationship between local government financial performance and unemployment. These results suggest that the main hypotheses proposed in this study are not supported by the empirical data. Improvements in regional fiscal performance have not been translated into productive economic activities and job creation. This study provides empirical evidence regarding the limitations of stewardship assumptions in local fiscal management, indicating that enhanced fiscal performance does not automatically lead to inclusive economic growth or a reduction in unemployment. Practically, the findings suggest that local governments should enhance the quality of spending allocation and strengthen productive sectors that support job creation.